Insurance risk management mechanisms in the system of higher education (Путеводитель предпринимателя, 2020)
The article reviewed and analyzed the financial risks of a modern market of services in the field ofhigher education, given their three-level classification. The author studied international experience of insurance in higher education. The paper makes proposals and recommendations for the implementation mechanisms of the commercial and mutual insurance in risk management system of higher education.